2016
DOI: 10.1039/c5ja00286a
|View full text |Cite
|
Sign up to set email alerts
|

A dual extraction technique combined with HPLC-ICP-MS for speciation of seleno-amino acids in rice and yeast samples

Abstract: MSPE combined with HF-LLLME for speciation of seleno-amino acids with high EFs and good anti-interference ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…39,40 Once inside the cells, Se (+4) ions are reduced to Se (−2) ions, then the Cd 2+ interacts with the seleno-precursors and forms QDs crystals. The main seleno-amino acids emerging during the biosynthesis, as the previous study suggested, 26 were detected by HPLC-ICP-MS. 41 In Figure 5, it is shown that the major seleno-amino acid peak heights in Δatp1 and WT samples were consistent with the fluorescence intensities between them ( Figure 2B). The result was proof that the accumulation of the seleno-precursor was an energy-consuming process.…”
Section: Discussionmentioning
confidence: 50%
“…39,40 Once inside the cells, Se (+4) ions are reduced to Se (−2) ions, then the Cd 2+ interacts with the seleno-precursors and forms QDs crystals. The main seleno-amino acids emerging during the biosynthesis, as the previous study suggested, 26 were detected by HPLC-ICP-MS. 41 In Figure 5, it is shown that the major seleno-amino acid peak heights in Δatp1 and WT samples were consistent with the fluorescence intensities between them ( Figure 2B). The result was proof that the accumulation of the seleno-precursor was an energy-consuming process.…”
Section: Discussionmentioning
confidence: 50%
“…In order to avoid the alteration of the sample during the preconcentration process, a solution of ethylenediamine was used as eluent. This method showed the following analytical performance for the analysis of Se compounds (SeCys 2 , MeSeCys, SeMet, and SeEt) in rice: linear range 158e278 mg L À1 , LOD 0.0075e0.013 mg L À1 and standard deviation 6.8e10.2% [90].…”
Section: Seleniummentioning
confidence: 94%
“…Selenium is an essential element with antioxidant and antitumoral effects [89], but the excess of this element can produce serious damage in the organism [90]. The toxicity of Se depends on the concentration and the chemical form, being more toxic selenite and selenate than the organic compounds such as selenoaminoacids, selenopeptides, selenoproteins, etc.…”
Section: Seleniummentioning
confidence: 99%
See 1 more Smart Citation
“…The second concern was the operation of rGO. Because the high-speed centrifugation-based collection of rGO dispersed in water is time-consuming, , GO or rGO has been combined with magnetic beads as a magnetic solid-phase extraction (MSPE) material in many studies for the extraction of a variety of molecules such as amino acids and proteins, making the collection of GO/rGO easier and faster. However, to the best of our knowledge, GO or rGO-based MSPE materials have never been used to extract miRNA before.…”
mentioning
confidence: 99%